Media VACON sebagai upaya meningkatkan kemampuan berpikir kritis matematis pada materi relasi dan fungsi - Ai Muna Nazla; Wahyu Hidayat; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
The creation of animated videos for mathematics lessons has so far focused solely on visual presentation, without linking the subject matter to students’ everyday experiences. Furthermore, the use of animated videos to teach relations and functions is still rarely discussed in media development research. Given this situation, a study will be conducted using an R&D method based on the ADDIE model to describe the development process, test the feasibility, and determine the effectiveness of the VACON media at a junior high school in West Bandung, involving 6 students in a pilot test and 25 students in a classroom test as the experimental sample. The study results showed a feasibility rating of 90.00% from the media expert, 92.50% from the content expert, and 87.50% from the language expert. The average N-Gain score was 0.82, which falls into the high category. Additionally, student responses to this media reached an average of 88.40%, indicating a “Very Practical” level of practicality in its implementation. Thus, the VACON media, utilizing Doratoon and Canva, has been proven to be valid, practical, and effective as an innovative solution.